The legacy of organochlorinated pesticides (OCPs), polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) in Chinese coastal seawater monitored by semi-permeable membrane devices (SPMDs). (December 2018) - Zhao, Dongmei; Zhang, Peng; Ge, Linke; Zheng, Gene J.; Wang, Xinhong; Liu, Wenhua; Yao, Ziwei
Abstract: Semi-permeable membrane devices (SPMDs) were applied to sample some Organochlorinated Pesticides (OCPs), Polycyclic Aromatic Hydrocarbons (PAHs) and Polychlorinated Biphenyls (PCBs) from the seawater of 14 Chinese coastal areas. The total concentrations of OCPs (∑16 OCPs), PAHs (∑15 PAHs) and PCBs (∑35 PCBs) were in the ranges of 489.2–2174, 589.4–53, 160, and 133.2–3658 ng/g lipid, respectively. The ∑15 PAHs varied significantly with the sampling locations, which were far higher in north Chinese coastal areas than in south areas, whereas ∑16 OCPs and ∑35 PCBs only slightly fluctuated along the entire coast line. Comparing SPMD to grab sampler, it was found that the distribution patterns of the PCBs and OCPs in seawater were generally similar. However, the compositional profiles of the PAHs, PCBs, DDTs and HCHs in SPMDs were slightly different to grab samplers and organisms. The SPMDs accumulated less lipotropic compounds, which are inclined to dissolve in water rather than in organisms. Graphical abstract: In the present study, the concentrations of PAHs, PCBs and OCPs in the seawater of Chinese coastal areas using SPMDs were reported. This figure illustrated that OCPs and PCBs did not vary significantly along the whole coast line, while PAHs residual levels in the Yellow Sea and East China Sea were relatively higher than other coastal areas in Chinese coasts. Highlights: The PAHs, PCBs and OCPs in entire Chinese coastline seawater using SPMD were reported. The concentrations of PAHs in north sea area were much higher than in south. The spatial distribution presented by SPMD was basically consistent to grab sampler. The OCs compositions and source diagnosis ratios in SPMDs were different to organisms.